FinTeh in the financial system of inclusiveness - LUTSIV, Bohdan (Scientific journal «World of Finance», 2019)
Introduction. The middle of 2000 years witness the shift in traditional economic development models to the concept of inclusive growth. The significant stratification of society and the growth of the share of the poor population due to financial and economic crises are the prerequisites for changing the paradigm of economic development of countries. According to the index of inclusive economic development (IDI) of 2018, published on the website of the World Economic Forum, Ukraine ranks 43rd among 74 developing countries. The introduction of the latest financial technologies in the banking system in recent years has significantly improved the qualitative characteristics of financial inclusiveness. The financial services market has radically changed. The boom of Finteh-startups is supported by smartphone population and penetration into all spheres of society of the fast Internet society.The purposeof the article is to assess the impact of financial technologies on the inclusive development of Ukraine in terms of banking sector cooperation with startup companies on the financial services market.Results. Concepts on the further development of the world economy in the long-term perspective are considered. Based on the analysis of modern economic literature, key points of inclusive growth are identified. In this context, the focus of the study is on financial inclusiveness. The emphasis is on strengthening the financial inclusiveness of the population in the adopted Strategy of the NBU by 2020. The most current trends of FinTeh in the world are described and the factors of development of FinTeh in Ukraine are analyzed. The given feature is the latest types of Finteh start-ups, challenges for the development of the FinTeh-market in Ukraine.Conclusions. The development of scientific thought and understanding of the transformation of social processes led to the transition from the concept of economism growth to the concept of inclusive development. The concept of inclusive development of the country is only part of the scientific discourse. Financial inclusiveness has not only financial but also social orientation. In Ukraine, FinTeh is in its infancy, the development of which is supported by a variety of initiatives and activities of the NBU. Given the current market demand, FinTeh solutions that are focused on financial inclusiveness and the mass market have the greatest potential for growth.